NILAI-NILAI PENDIDIKAN DALAM TEKS CERITA RANDAI “MALANGGA SUMPAH” KARYA LUKMAN BUSTAMI GRUP RANDAI BINTANG TAMPALO KENAGARIAN PADANG LAWEH KABUPATEN SIJUNJUNG - Helki Syuriadi; Hasanuddin WS; Ngusman . (Bahasa, Sastra, dan Pembelajaran, 2014)
Abstract: The pourpuse this study were to describe the values of education in Story script of Randai titled “Malangga Sumpah” written by Lukman Bustami. The research data was collected by qualitative data, The result of this study is four values of education values in randai script ”Malangga Sumpah” in by Lukman Bustami there are believe and religious, integrity, caring, and honesty. Kata kunci: nilai-nilai pendidikan, teks cerita randai, Lukman Bustami.